Reading as a cultural practice: concepts for the study of schoolbooks (Educação e Pesquisa, 2001)
This article presents a perspective on the study of classroom reading practices based on the work of French social historian Roger Chartier. This scholar conceives the reading as a cultural practice that draws on shared artifacts, behaviors, attitudes and meanings. A basic tenet of his research is that "the acts of reading that give texts their plural and mobile meanings take place at the point of encounter between specific manners of reading and the reading protocols contained in the object that is read" (Chartier 1993:80). His analysis centers on the material aspects of the book, and on reading practices, as well as on the text itself. This approach is illustrated with an analysis of a lesson in a Mexican rural school. The teacher read a story from the textbook, closely following the implicit protocol. However, both the textbook layout and actual ways of reading influenced the outcome of the lesson. The article discusses the changing relationships to the written language that students construct through schooling. The history of literacy places a significant inflection between the intensive reading of single texts and the appearance extensive reading of multiple and changing texts, among them schoolbooks. However, Chartier argues that the process of appropriation always transforms cultural practices and meanings in given contexts. Attention to the everyday manners of reading in classrooms may reveal multiple appropriations of textbooks that lead to diverse relationships-some more inclusive, others rather exclusive.